2002
DOI: 10.1002/smi.929
|View full text |Cite
|
Sign up to set email alerts
|

Self‐esteem, personality and post traumatic stress symptoms following the dissolution of a dating relationship

Abstract: The present study aimed to ascertain the extent to which people, following the dissolution of a dating relationship, experienced post traumatic stress symptoms. It also aimed to investigate the relationship between post traumatic stress and self-esteem and personality. The hypotheses were that there would be a severe degree of post traumatic stress symptoms experienced by the present samples, and that the personality factor, in particular, neuroticism, and low self-esteem would be associated with the samples' … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
43
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 46 publications
4
43
0
1
Order By: Relevance
“…It was shown that exposure to trauma may cause sleep disturbance (Babson & Feldner, 2010), but insomnia and nightmares are also associated with an increased risk for onset and continuance of PTSD (Wright, Britt, Bliese, Adler, Picchioni, & Moore, 2011), so they may serve as risk factors for PTSSs. In general, the high positive correlations between GHQ-28 dimensions and PTSSs confirmed in our study among patients with gynaecological pathology are in line with the results of previous studies (Chung et al, 2002;Taubman-Ben-Ari et al, 2001). Summing up, emotional reactivity and anxiety symptoms increase PTSS intensity in gynaecological patients, whereas lovability as a dimension of self-esteem may serve as a protective factor against intensification of PTSSs.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…It was shown that exposure to trauma may cause sleep disturbance (Babson & Feldner, 2010), but insomnia and nightmares are also associated with an increased risk for onset and continuance of PTSD (Wright, Britt, Bliese, Adler, Picchioni, & Moore, 2011), so they may serve as risk factors for PTSSs. In general, the high positive correlations between GHQ-28 dimensions and PTSSs confirmed in our study among patients with gynaecological pathology are in line with the results of previous studies (Chung et al, 2002;Taubman-Ben-Ari et al, 2001). Summing up, emotional reactivity and anxiety symptoms increase PTSS intensity in gynaecological patients, whereas lovability as a dimension of self-esteem may serve as a protective factor against intensification of PTSSs.…”
Section: Discussionsupporting
confidence: 92%
“…With respect to mental health, Chung et al (2002), using the General Health Questionnaire (GHQ-28), found a positive correlation between PTSSs and all mental health dimensions (somatic problems, anxiety, social dysfunction and depression) following the dissolution of a dating relationship. Chung, Berger, Jones, and Rudd (2008) observed higher levels of the aforementioned mental health dimensions in older myocardial infarction patients with full PTSD compared with a no-PTSD group (see also Horsham & Chung, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The potential negative impact of a non-marital breakup on mental health extends beyond elevated levels of distress; the experience of a relationship breakup has been found to predict the initial onset of major depressive disorder in adolescents (Monroe, Rohde, Seeley, & Lewinsohn, 1999). Following the dissolution of a dating relationship, many people may even experience posttraumatic stress symptoms, such as intrusive thoughts and avoidance behaviour (Chung et al, 2002). In fact, Chung et al (2002) found that almost three quarters of their sample of individuals who had experienced a relationship breakup scored high on a measure of posttraumatic stress symptoms (the Impact of Event Scale; Horowitz, Wilner, & Alvarez, 1979).…”
mentioning
confidence: 99%
“…Following the dissolution of a dating relationship, many people may even experience posttraumatic stress symptoms, such as intrusive thoughts and avoidance behaviour (Chung et al, 2002). In fact, Chung et al (2002) found that almost three quarters of their sample of individuals who had experienced a relationship breakup scored high on a measure of posttraumatic stress symptoms (the Impact of Event Scale; Horowitz, Wilner, & Alvarez, 1979).…”
mentioning
confidence: 99%
“…(Note that this could be related to legal barriers to a) homosexuals wishing to get married and b) heterosexual married couples wishing to break up.) If homosexual relationships are less stable, it could pose a risk to mental health to nonheterosexuals given that relationship dissolution is a major life stressor that can provoke psychiatric problems (Chung et al 2002).…”
Section: Relationship Stabilitymentioning
confidence: 99%